AA Enterprise : Toothfairy Toothbrush / Adriana Farhana Nasir - Nasir, Adriana Farhana (2020)
AA Enterprise starts its operation in Kuala Terengganu which has been opened up to public on 26 June 2020. It is a partnership company and focusing on selling the technology based product which is electric toothbrush and its other functional. The company is owned and managed by its four partners and expects to catch interest of regular customer with its new innovation products. AA Enterprise main product is Toothfairy toothbrush with an innovation of automatic toothpaste refill. This toothbrush is very convenient and practical since it can bring anywhere. The user can charge the toothbrush using USB cable which compatible with global voltage and universal USB port, so they do not have problem to bring toothbrush when travel. The product has a unique and quality design with an affordable price. The company aims to offer its new product at a competitive price to meet demand of middle to higher income local market area.